A NEW CASE OF MELANIC JAGUAR, Panthera onca (CARNIVORA: FELIDAE) FROM PERU - RENGIFO, Edgardo M. (2020)
We report a new case of melanism in jaguars, Panthera onca, using camera traps in the Parque Nacional Ichigkat Muja - Cordillera del Cóndor, Amazonas - Peru. This report increases our knowledge related to polymorphic variations found in jaguars.